1993
DOI: 10.1007/bf00216445
|View full text |Cite
|
Sign up to set email alerts
|

Data on the CGG repeat at the fragile X site in the non-retarded Japanese population and family suggest the presence of a subgroup of normal alleles predisposing to mutate

Abstract: The fragile X mutation is the result of amplification in the repeat number of p(CGG)n in FMR-1; alleles with more than 52 repeats have been shown to be so unstable as to mutate in the repeat number in almost every transmission. To improve our understanding of mutations in normal alleles of FMR-1, the following studies were carried out in the Japanese population: a study on length variation in the repeat to determine the allele distribution of the repeat length in a non-retarded population, family studies to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 18 publications
6
30
2
Order By: Relevance
“…Our calculations thus confirm and extend several earlier reports that the frequency of premutation carriers differs for Asian as compared to non-Asian populations (see, e.g., Arinami et al, 1993;Hofstee et al, 1994;Nanba et al, 1995;Otsuka et al, 2010). Our analysis also yielded evidence that there is heterogeneity among non-Asian populations worldwide (adjusted p-value of 0.0014; Table 5), though at a lesser degree than that observed for Asian as compared to non-Asian populations, suggesting the possibility of variation at several geographic scales.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Our calculations thus confirm and extend several earlier reports that the frequency of premutation carriers differs for Asian as compared to non-Asian populations (see, e.g., Arinami et al, 1993;Hofstee et al, 1994;Nanba et al, 1995;Otsuka et al, 2010). Our analysis also yielded evidence that there is heterogeneity among non-Asian populations worldwide (adjusted p-value of 0.0014; Table 5), though at a lesser degree than that observed for Asian as compared to non-Asian populations, suggesting the possibility of variation at several geographic scales.…”
Section: Resultssupporting
confidence: 92%
“…Several reports indicate differences among populations in the distribution of fragile X alleles into the normal, premutation and full-mutation size classes (see, for example, Arinami et al, 1993;Barros-Núñez et al, 2008;Hofstee et al, 1994;Nanba et al, 1995;Otsuka et al, 2010;Peprah et al 2010). Asian and non-Asian populations, in particular, have been reported to exhibit substantial differences, with markedly lower frequencies of premutation-and fullmutation carriers observed in Asian populations (Arinami et al, 1993;Hofstee et al, 1994;Nanba et al, 1995;Otsuka et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Arinami et al, 15 on nonretarded Japanese subjects, showed (CGG) 28 to be the most frequent allele in their population, and reports 16±18 on the Chinese population showed the most frequent allele to be (CGG) 29 among their normal subjects. A similar distribution pattern was observed by Richards et al 19 in a study on the different ethnic populations of the world.…”
Section: Variations Of Cgg Repeats At the Fm R1 Locus In Normal Subjectsmentioning
confidence: 99%
“…Among Asian populations these studies have been largely limited to the North Asian populations of China and Japan (Arinami et al 1993 ;Richards et al 1994 ;Zhong et al 1994 ;Poon et al 1999), although one study has reported the analysis of FMR1 and FRAXAC1 in 31 samples from the Kadazan population of Sabah, Malaysian Borneo (Kunst et al 1996). Comparison of published allele frequencies for short tandem repeats within the fragile X locus in North Asian, Caucasian and African populations have identified clear differences between these populations (Zhong et al 1994 ;Chiurazzi et al 1996 b).…”
mentioning
confidence: 99%